PENURUNAN TIMBULAN LIMBAH DENGAN MODIFIKASI SISTEM AIR STARTING MESIN MAIN BOOSTER PUMP - Emin Haris; Arsanto Wibowo Arsanto Wibowo (P3M Politeknik Negeri Indramayu, 2016)
Hazardous and toxic waste (LB3) is one of the environmental impacts that must be managed in the Republic of Indonesia in accordance with Indonesian Law No. 32 / 2009 on the Protection and Environmental Management Article 58. B3 is the residue of a business and / or activities that contain hazardous and toxic. Hazardous and Toxic waste generated shall be reduced in accordance with Article 10 of Indonesian Regulation No. 101 / 2014 on the Management of Hazardous and Toxic Waste. One sector that has a real contribution in donating B3 waste generation is the energy sector. PT Pertamina, which is engaged in the energy sector undertake efforts to reduce hazardous waste generation on the activities of pumping the fuel at the Balongan Fuel Terminal. The case studies conducted in Balongan. Starter activities that were previously used accumulator pose as hazardous waste to be modified. Reduced waste generation by Fuel Terminal Balongan by modifying the diesel engine starter system method with compressed air.